Wildlife Interactions on Baited Places and Waterholes in a French Area Infected by Bovine Tuberculosis - Payne, Ariane; Philipon, Sixtine; Hars, Jean; Dufour, Barbara; Gilot-Fromont, Emmanuelle (Frontiers in Veterinary Science, 2017)
Interactions among wildlife species are major drivers for the transmission of multi host pathogens, such as Mycobacterium bovis, which also affect livestock. Although France is officially free from bovine tuberculosis (bTB), some areas are still harbouring infection in cattle and wildlife. We aimed at characterizing the visits of susceptible wild species (badger, red deer and wild boar) at baited places and waterholes, considered as possible hotspots for contacts. We described the visits in terms of frequency, duration and number of individuals and studied the influence of the season. Then we estimated the frequency of intraspecies and interspecies interactions occurring at baited places and waterholes which may lead to bTB transmission, including direct and indirect contacts through the soil or water. We used camera-traps placed on baited places and waterholes on 13 locations monitored during 21 months. The number of visits, their duration and the number of individuals per visit were analysed by generalized linear mixed models for each targeted species. The frequency of the interspecies and intraspecies interactions were also analysed separately. The season, the type of site (baited place or waterhole) and the location were the explanatory variables. Badgers’visits and interactions were more frequent than for other species (mean: 0.60 visit / day and 5.42 interactions / day) especially on baited places. Red deer only visited waterholes. Wild boars visited most often baited places in spring-summer and waterholes in autumn-winter. They came in higher number than other species, especially on baited places. Direct interactions were uncommon. The most frequent interspecies interactions occurred between red deer and wild boar (mean: 4.02 interactions / day) Baited places and waterholes are important interfaces between the different wild species involved in the bTB multi host system in this area. They can thus promote intraspecies and interspecies bTB transmission. Baiting ban should be carried on and management of waterholes should be considered as tool to limit the spread of bTB in wildlife